Multiple myeloma. An unusual case. - Silva, F (1992)
We describe the case of a 75 year old male patient, hospitalized because of sudden paraplegia. The radiological tests performed, revealed degenerative changes of the entire vertebral spine, osteolytic lesions of the seventh cervical and first two thoracic vertebrae, and lacunar lesions of the others. The erythrocyte sedimentation rate, total proteins and its electrophoretic study, as well as quantification of serum immunoglobulins were found to be normal. Regardless of these results, we continued our investigation in order to diagnose or exclude multiple myeloma (MM), which was confirmed by serum and urinary immunoelectrophoresis, that revealed monoclonal gammopathy IgG, K with low value of serum IgG and very high urinary values of Bence Jones K, and by the histological analysis of the necropsy material. In conclusion, we report a case where the probability of an alteration of the controlling immunological mechanisms must be considered. We suggest that there is a heavy chain suppression of the malignant clone, that would explain its very low value in peripheral blood. These findings associated to the absence of light chains in serum, have lead to a particular laboratorial expression of this myeloma.